NiCo LDH in situ derived NiCoP 3D nanoflowers coupled with a Cu3P p–n heterojunction for efficient hydrogen evolution. Issue 32 (6th August 2021) - Yang, Mengxue; Li, Yanbing; Yan, Teng; Jin, Zhiliang
Abstract : A p–n heterojunction of Cu3 P coupling with NiCoP nanoflower has been synthesized. The heterojunction promotes the separation efficiency of photogenerated carriers and enhances photocatalytic hydrogen production activity. Abstract : With the extensive consumption of non-renewable energy sources, storing solar energy as chemical energy has aroused people's wide concern. In this study, we successfully developed a novel Cu3 P@NiCoP composite photocatalyst to produce hydrogen by splitting water under visible light irradiation. Both the building of a p–n heterojunction between Cu3 P and NiCoP and the three-dimensional nanoflower structure of NiCoP play a vital role in improving the performance of the catalyst. On the one hand, the coupling of Cu3 P and NiCoP built a p–n heterojunction at the photocatalyst interface, and the heterojunction could promote the separation efficiency of photogenerated carriers and prolong the life span of charges, therefore enhancing the photocatalytic hydrogen production activity. On the other hand, the excellent catalytic performance of the photocatalyst was benefited by the flower-like microsphere structure of NiCoP, which could provide abundant active sites and a large specific surface area, and promote the adsorption of protons by the photocatalyst. Besides, the phosphating degree of the precursors and the ratio of Cu3 P and NiCoP were adjusted to get the best photocatalyst for hydrogen production, and the H2 production of the optimal catalyst could reach 8897.44 μmol h −1 g −1 . This work provides a new understanding for the rational design of heterojunction photocatalysts for outstanding hydrogen production performance.